Implementation of presidential regulation no. 76 of 2013 on public service complaint managementby the provincial government of West Sumatra - Yunesa Rahma; Dasman Lanin; Afriva Khaidir (International Conferences on Educational, Social Sciences and Technology)
This research synthesizes the theory of applying Charles Edwards III, with 4 variables; communication, disposition, resources and organizational structure. This team principally assisted the Governor in overseeing and managing complaints relating to public services. This team has the main duty of handling public service complaints for the people in West Sumatra. Provincial government of West Sumatera has not been sufficient in implementing Presidential regulation No. 76 of 2013 on Public Service Complaint Management. In effective TP4 performance in accepting public complaints has an effect on the aims and objectives of the Presidential Regulation. TP4 West Sumatera Province more dominates the prevention performance, TP4 conducts guidance and monitoring both through working visit as well as Provincial Service Competency Assessment Team at Provincial level.